Research Paper on Human Rights Protection for Women Workers on Leave - Florencia, Cherlyne Baby; Chandra, Jessica; Rasji, Rasji (CV. Rayyan Dwi Bharata, 2023)
Human Rights is a legal and normative concept which states that humans have their rights that are inherent in themselves, which are universal and can be applied anytime, anywhere and to anyone. In principle, human rights remain attached to women and men. Women as a group in society within a country, is a group that is also obliged to get guarantees for their basic rights, especially for female employees who work both in private companies and within the scope of government. Every human being has rights, including workers, one of which is obtaining the right to leave, namely the right for workers not to work for a certain period of time. Specifically for women, based on Law No. 13 of 2003, female workers have more rights to apply for leave, namely maternity leave and menstruation leave. There is a rule that female workers are entitled to leave during pregnancy at least 1.5 months before the expected date of delivery and 1.5 months after delivery. In addition, female workers are also entitled to 2 days of menstruation leave in each working month. Maternity rights are human rights that are specifically attached to women because of their reproductive functions, such as menstruation, pregnancy, childbirth and breastfeeding. The results show that government regulations are very helpful in reducing the productivity of women during pregnancy and menstruation.